(untitled) (Biological Sciences - PJSIR, 2004)
The electrical conductivity ? and the dielectric constant ?’ were measured at a frequency of 1 KHz on pressed pellet of CaF2in the temperature range 373-873°K. The pressure applied for preparing the sample varied from 3 to 5 tons/cm2 on circular disk of 2.5 cm diameter and 0.45 cm thickness by hydraulic press. In the temperature range investigated the conductivity data exhibited to activate regions yielding activation energies of 0.532 ev and 0.42 ev. The region I called intrinsic region and region II is extrinsic region. The effect of temperature and the hydrostatic pressure on the real and imaginary part of the dielectric constant for this sample has been studied. The dielectric constant curve shows a slow increase of dielectric constant up to temperature 473°K and above this temperature, a fast increase in ?’, which may be attributed to lattice expansion and polarizability of constituent ions. At high temperature in the dielectric, two points of phase transition are attained. In the present study, it has been found that within the reported temperature range the dielectric constant and dielectric loss are predominately determined by the motion of the defects. The activation energy deduced from the dielectric studies is in good agreement with that obtained from the present electrical conductivity data.